Does Equality Promote Growth? - Stefan Fölster; Georgi Trofimov (The Research Institute of Industrial Economics (IUI), 1996)
Several recent articles claim that pre-tax income equality promotes growth. Equality is argued to dampen demand for redistributive economic policies that tax returns to growth-enhancing activities such as investment. These results rest heavily on the assumption that pre-tax income equality is an exogenous parameter. We suggest that taking account of endogenous influences on pre-tax income equality changes both theoretical and empirical conclusions significantly. First, we extend previous theoretical models by letting income equality be endogenously determined. This leads to the conclusion that equality does not cause growth, although there may be a positive or negative correlation. Second, it is shown that previously reported positive empirical relationships between equality and growth turn insignificant or weakly negative when the omitted variables suggested by our model are taken into account.
Keywords: H20; H21; O40; O40; 330; TAX POLICY; ECONOMIC GROWTH; INVESTMENTS; Einkommensverteilung; Wirtschaftswachstum; Overlapping Generations; Theorie